The The relationship between spiritual intelligence and components of burnout in female teachers - H Zareei mahmoodabadi; N Sedrpooshan (طب کار)
Background: Spiritual intelligence is the ability to apply spiritual values and updated so that they improve daily functioning and the individual's physical and mental health. The purpose of this study was to investigate the relationship between spiritual intelligence components of burnout in teachers of Yazd city. Methods: The research method was descriptive– correlation. Population of this research consisted of female teachers. 133 teachers were selected by using cluster sampling. The instruments of this research were Spiritual intelligence questionnaire and Burnout Inventory. Results: The results showed that the frequency and intensity of emotional exhaustion and depersonalization frequency was negative and showed a significant relationship with spiritual intelligence (P0.05). Conclusion: The training component of spiritual intelligence can prevent some aspects of burnout in teachers.